What was the Direction of the Reform of the PRL (Polish People’s Republic) Economy in the Eighties? - Kaliński, Janusz (Studia Historiae Oeconomicae, 2020)
In the 1980s, the communist authorities of Poland, forced by the dire economic and social situation, undertook a number of attempts to reform the centrally managed economy. By deciding on limited liberalization, they simultaneously secured the economic foundations of the government, which was dominated by the public sector. The Polish version of perestroika was, thus, implemented in order to balance the economy. However, like the Soviet model, it was a tactical move, essentially to consolidate the centrally managed economy. The economic hybrid that emerged from the partial reforms, contrary to the intentions of its creators, did not weaken, but rather strengthened deep crisis phenomena. Their inhibition became the main goal of the democratic government formed in 1989 and the radical economic reforms associated with the name of Leszek Balcerowicz. The departure from the reforms of the centrally managed economy and the undertaking of consistent market transformation resulted in measurable economic successes. They were particularly visible against the background of the economy of Belarus, Russia and Ukraine, whose authorities had abandoned comprehensive and consistent market reforms.